OBAT TRADISIONAL SEBAGAI ADJUVAN UNTUK MENINGKATKAN KUALITAS HIDUP DAN PRODUKTIVITAS WARGA DESA KARANGANYAR PENDERITA DIABETES MELITUS - Mahfur, Mahfur; Khasanah, Nunung; Nahdliyyah, Ade Irma; Arni, Aneke Desvita; Rohmaniah, Salis Alyatur (Jurnal Abdi Insani, 2025)
Karanganyar Village, Batang District, has great potential for utilizing traditional medicinal plants to improve community health. Cases of diabetes mellitus in the area have increased due to unhealthy lifestyles and excessive sugar consumption. Local plants such as bay leaves (Syzygium polyanthum), bitter leaf (Andrographis paniculata), cinnamon (Cinnamomum verum), and turmeric (Curcuma xanthorrhiza) possess proven antihyperglycemic effects and are safe for use as adjuvant therapy. This community service program aimed to educate and empower the community to independently utilize local resources. The activity, held at the Karanganyar Village Hall with 30 PKK women participants, employed pre-tests, material presentations, interactive discussions, and post-tests to assess knowledge improvement. Results showed that participants initially lacked understanding of adjuvant concepts and medicinal plant utilization. However, after the sessions, all participants demonstrated significantly better comprehension and confidence in applying traditional medicine to support diabetes management. The high engagement level indicated that the materials were relevant and beneficial to the community’s needs. This program effectively enhanced public knowledge of traditional medicine as an adjuvant for diabetes mellitus and has the potential for independent application in local health practices.